Asymmetry of lower extremity force and muscle activation during knee extension and functional tasks. Issue 3 (11th May 2017) - Bond, Colin W.; Cook, Summer B.; Swartz, Erik E.; Laroche, Dain P.
ABSTRACT: Introduction: Strength and power asymmetries of >10% may negatively impact physical function. Methods: Twenty‐four healthy participants, 30–60 years of age, were assessed for muscle power asymmetry during isokinetic knee extension and ground reaction force asymmetry during chair‐rise and vertical jump tasks. Neuromuscular activation asymmetry and coactivation of vastus lateralis (VL) and biceps femoris (BF) were assessed in each condition. Symmetric (SG) and asymmetric (AG) groups were identified using a 10% knee extension power asymmetry criterion. Results: The AG had greater chair‐rise rate of force development asymmetry ( P = 0.003, d = 1.29), but a similar chair‐rise and vertical jump peak force asymmetry as the SG. Large group effects were found for VL activation asymmetry during knee extension ( P = 0.047, d = 0.87), BF activation asymmetry during vertical jump ( P = 0.015, d = 1.12), and strong leg coactivation during vertical jump ( P = 0.028, d = 0.96). Conclusions: Compensation for muscle power asymmetry may occur during functional tasks, potentially through differential activation of strong and weak leg muscles. Muscle Nerve 56 : 495–504, 2017